Hubungan antara Frekuensi Masturbasi dengan Indeks Prestasi Belajar pada Mahasiswa Fakultas Kedokteran Universitas Sebelas Maret - Gerry Febrian Rizaldi; . Makmuroch; Istar Yuliadi (Nexus Kedokteran Klinik, 2014)
Background: Masturbation is generally defined as the deliberate stimulation of the genital organs is performed on to obtain sexual pleasure and satisfaction. Masturbation can cause disruption of concentration on a particular teens. For a student or students, the important factor is the ability to support the achievement of learning memory and concentration as internal factors. The purpose of this study was to determine the relationship between the frequency of masturbation with the index student learning achievement in medical school, Sebelas Maret University. Methods: This research is a descriptive analytic cross with sectional study approach. Samples were taken using a total random sampling method. Researchers took a sample of 170 people. Data were obtained by questionnaire. Data were analyzed using the Statistical Product and Service Solutions (SPSS) 17 for Windows statistical test "Chi Square". Results: A total of 139 respondents consisted of 65 respondents to the frequency of masturbation > 2x a week and 74 respondents with masturbation frequency ? 2x a week. Chi Square test showed statistical calculation results of p < 0.05 is p = 0.000; OR = 1.23. Conclusions: The analysis showed there is a relationship between the frequency of masturbation and the index student learning achievement in this research Keywords: masturbation index student learning achievement students